Realitea podcast / Abdul Hamid Saifuddin and Mohd Yusof Zulkefli - Saifuddin, Abdul Hamid; Zulkefli, Mohd Yusof (2022)
The prime objective of this podcast series is to connect a local problem to a potential solution via roundtable discussion with field experts. The chief idea is to move beyond raising awareness about the particular problem to get the community to do something about it. Vast technological developments and pressing issues in Malaysia gave birth to curious Malaysians shelved under the Generation Z bracket. Podcasting gave them a voice to opportune themselves to shed light on things that matter. It gave young Malaysians to discuss real issues in search of workable, sustainable solutions. In order for the podcast to have a clear sense of direction in terms of the conversation that is about to be discussed, it has been decided that it should be centered around the United Nations 17 Sustainable Development Goals (17 SDG). Through the podcast, the contents are targeted to audiences within their peers to expose them to the problems and its effect on the community both in short and long term. As a result, several prime examples to the testament of the podcast successes are through its visibility.